Regulation of Hyphal Growth and N-Acetylglucosamine Catabolism by Two Transcription Factors in Candida albicans. Issue 1 (1st May 2017) - Naseem, Shamoon; Min, Kyunghun; Spitzer, Daniel; Gardin, Justin; Konopka, James B
Abstract: The amino sugar N-acetylglucosamine (GlcNAc) is increasingly recognized as an important signaling molecule in addition to its well-known structural roles at the cell surface. In the human fungal pathogen Candida albicans, GlcNAc stimulates several responses including the induction of the genes needed for its catabolism and a switch from budding to filamentous hyphal growth. We identified two genes needed for growth on GlcNAc ( RON1 and NGS1 ) and found that mutants lacking these genes fail to induce the genes needed for GlcNAc catabolism. NGS1 was also important for growth on other sugars, such as maltose, but RON1 appeared to be specific for GlcNAc. Both mutants could grow on nonfermentable carbon sources indicating that they do not affect mitochondrial function, which we show is important for growth on GlcNAc but not for GlcNAc induction of hyphal morphogenesis. Interestingly, both the ron1 Δ and ngs1 Δ mutants were defective in forming hyphae in response to GlcNAc, even though GlcNAc catabolism is not required for induction of hyphal morphogenesis. The ron1 Δ mutant showed a partial defect in forming hyphae, which was surprising since it displayed an elevated level of filamentous cells under noninducing conditions. The ron1 Δ mutant also displayed an elevated basal level of expression of genes that are normally upregulated during hyphal growth. Consistent with this, Ron1 contains an Ndt80 -like DNA-binding domain, indicating that it regulates gene expression. Thus, Ron1 is a key new component of the GlcNAc response pathway that acts as both an activator and a repressor of hyphal morphogenesis.